PELATIHAN HYPNOTHERAPY UNTUK MENURUNKAN TINGKAT KECEMASAN DAN MENINGKATKAN KONSENTRASI PADA ATLET BOLA VOLI SMK AL-HUDA SARIWANGI KABUPATEN TASIKMALAYA - Agus Mulyadi; Juhrodin Juhrodin; Defri Mulyana (Jurnal Pengabdian Siliwangi, 2018)
The importance of paying attention to the level of anxiety when competing on an athlete is when an athlete is overwhelmed with high anxiety, and decreased concentration causes the athlete difficulty in controlling the movement, the game becomes ugly, unable to apply the strategy because it does not know what to do so it will ultimately affect the performance ), Self-confidence becomes diminished and even disappears.Therefore, the use of hypnotherapy method is very important to reduce the level of anxiety and increase the concentration of athletes during the game. Hypnotherapy consists of two kinds of hypnosis and self-hypnosis. Self-hypnosis can be defined as self-suggestion (self suggestion), because basically when doing self-programming means being mensugesti self to match what is expected (Sugara, 2013: 35). The difference between hypnosis and self-hypnosis is the subject of hypnosis. If in hypnosis the person in hypnotherapy is guided by a therapist who has knowledge and abilities in hypnosis while self-hypnosis guides oneself to enter the hypnotic state, then do self-suggestion which is beneficial to him and can add concentration power.